The influence of structural heterogeneity of hollow glass microspheres on physical and chemical processes of the formation of materials and coatings - Казимиренко, Юлия Алексеевна (Technology audit and production reserves, 2015)
The physical and chemical processes of formation of new compositions based on hollow glass microspheres are discussed in the article. The aim – to determine the influence of the structural heterogeneity of hollow glass microspheres of sodium silicate composition on the physical and chemical processes of formation of hot aluminum-matrix materials and coatings based on electric-Sv-AMg5 and Sv-08G2S. Researches are performed by electronic and optical microscopy, X-ray diffraction and electron microprobe analysis. The basis of the laws of formation of the new-metal materials and coatings based on new knowledge about the mechanisms of formation of a liquid phase based on the structural heterogeneity of hollow glass microspheres that can predict the physical and chemical processes at the metal – glass boundary surface. The theoretical researches allow us to establish the distinctive features of the structure formation depending on the method of preparing the compositions, and are aimed at improving their competitiveness. The results are used to predict the mechanical properties of the x-ray and metal-glass materials and coatings for their further use for the manufacture of structures of biological protection of ships and floating structures, for the transportation and storage of radioactive substances.